Serine Protease 3 Promotes Progression of Diffuse Large B-Cell Lymphoma and Serves as a Novel Prognostic Predictor - Zheng, Liangda; Wang, Xianting; Zheng, Weizhi; Huang, Hui (Disease Markers, 2022)
Diffuse large B-cell lymphoma (DLBCL) ranks among the most prevalent malignancies of the lymphohematopoietic system in adults. The PRSS (Serine Protease) protein family members had been reported to be involved in carcinogenesis as well as tumor progression. Here, we aimed to explore the expression profile of PRSS3 in DLBCL and investigate its clinical significance as well as detailed functions. We retrospectively enrolled 155 DLBCL patients from our hospital and tested protein expression level of PRSS3 through immunohistochemical staining. Accordingly, PRSS3 was highly expressed in certain DLBCL tissues. Chi-square test revealed that higher PRSS3 expression was correlated with advanced Ann Arbor stage, elevated serum LDH level, and higher International Prognostic Index. Moreover, univariate and multivariate analyses confirmed that higher PRSS3 can act as an independent unfavorable prognostic predictor for DLBCL. Two human DLBCL cell lines, SUDHL10 and OCI-LY3, were subjected for knockdown assays, followed by phonotype tests including proliferation and invasion. According to the cellular experiments, PRSS3-knockdown resulted in impaired DLBCL proliferation in the two cell lines above. Taken together, PRSS3 is a novel prognostic factor for DLBCL, which functions by multiple signaling pathways.